Direct and Inverse Approximation Theorems for Baskakov Operators with the Jacobi-Type Weight - Guo Feng (Abstract and Applied Analysis)
We introduce a new norm and a new K-functional Kφλ(f;t)w,λ. Using this K-functional, direct and inverse approximation theorems for the Baskakov operators with the Jacobi-type weight are obtained in this paper.